TRANSMISI HARGA JAGUNG DI PROVINSI LAMPUNG - Rati Purwasih; Muhammad Firdaus; Sri Hartoyo (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Corn is one of the leading commodities in Lampung Province. The average corn price received by farmers (producers) from January 2009 to December 2014 amounted to Rp 1.820 per kilogram, while the average price of corn at the consumer level was at Rp 3.205 per kilogram. Corn prices at the consumer level are more volatile when compared with the price of corn at the producer level. The purpose of this study are to analyze the transmission of corn prices from the consumer level to the producer level in Lampung Province. The data used was a monthly time series data from January 2009 to December 2014 (72 month). Asymmetric Error Correction Model (AECM) developed by von Cramon-Taubadel and Loy (1996) was used to analyze corn price transmission from the consumer level to the producer level. Causality test results indicate that corn prices at the consumer level affect the formation of corn prices at the producer level. From AECM estimates obtained, the short run corn price transmission from the consumer level to the producer level was asymmetric. However, the long-run transmission of corn prices from the consumer level to the producer was symmetric. After the Wald test, results obtained showed that there was no prove of asymmetric price transmission from the consumer level to the producer level in the long run.